The Effectiveness of HRM Strategies in Sustainability of Non-Governmental Organizations: A Case Study in World Vision, Mongolia - Sambuu, Javkhlan (2013)
This research gives the perspective on sustainability of NGOs through human resources management strategies and its best practice. The purpose of this research is to examine the effectiveness of Human Resources strategies in sustainability of NGOs and World Vision, Mongolia and its human resource strategies explored in this research. There were seven semi-structured in-depth interviews conducted with the managers and employees of World Vision Mongolia. The data were analyzed as template analysis with four themes (i) organizational culture (ii) organizational support (iii) employee satisfaction and (iv) job security. The findings mentioned that the organizational support is the key trigger among the other themes and recommendations have made upon the barriers and challenges that have been addresses in the research.